2010
DOI: 10.1016/j.juro.2010.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor-Free Status in Repeat Resection Before Intravesical Bacillus Calmette-Guerin for High Grade Ta, T1 and CIS Bladder Cancer

Abstract: Tumor-free status at repeat transurethral bladder tumor resection improves the bacillus Calmette-Guerin response rate and delays tumor recurrence. During followup recurrence in residual tumor-free patients develop more likely as low grade lesions than in patients with residual tumor at repeat transurethral bladder tumor resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 16 publications
3
21
0
2
Order By: Relevance
“…Interestingly, a risk factor for intravesical recurrence in our series was the presence of pTis/a residual tumors on the second TUR, but not tumor size nor the presence of concomitant CIS. The same tendency was shown in the previous report including the patients given a second TUR (23). In this study, most patients (75%) had received intravesical BCG therapy after the second TUR, and we thought that this high rate of BCG therapy resulted in a higher 3-year RFS rate than in the other studies shown in Table 3.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, a risk factor for intravesical recurrence in our series was the presence of pTis/a residual tumors on the second TUR, but not tumor size nor the presence of concomitant CIS. The same tendency was shown in the previous report including the patients given a second TUR (23). In this study, most patients (75%) had received intravesical BCG therapy after the second TUR, and we thought that this high rate of BCG therapy resulted in a higher 3-year RFS rate than in the other studies shown in Table 3.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were reported in a previous study in which tumour-free status at repeat TUR was associated with fewer recurrences, longer times to tumour recurrence and less progression. 12 These findings underscore the importance of complete resection of all visible or suspicious lesions on the outcome of patients with NMIBC.…”
Section: Discussionmentioning
confidence: 85%
“…81,82 Although the value of re-resection is often stated, whether or not it leads to an actual improved response to BCG is not clear. The studies evaluating repeat vs. single TURBT in this regard 83,84 should not be considered conclusive. While the evidence does support re-resection for most patients, the panel did note that there could be select situations, such as resection of a small T1 tumour with muscle by an experienced surgeon who is confident that the extent and depth of the resection is adequate, that re-resection may not be necessary.…”
Section: Discussionmentioning
confidence: 99%